ASSESSMENT OF THE NUTRITIONAL VALUES AND PROXIMATE ANALYSIS OF THE AFRICAN BLACK OLIVE (Canarium schweinfurthii linn) (ATILI) OIL SOLD AT DANTSE, GANAWURI MARKET OF RIYOM LOCAL GOVERNMENT AREA, PLATEAU STATE, NIGERIA - Dasat, George Shwamyil; Kum, Folakemi Olusola; Dakum, Esther Ngal (FUDMA Journal of Sciences, 2026)
The olive tree has global significance and high economic value because of its oil, which has a centuries-long history in the Mediterranean diet and is widely consumed worldwide. Alongside the economic value to the national economy of many countries, olive oil also serves as an important food in terms of its nutritional value. Olive oil extracted from the ripe fruit (Canarium schweinfurthii) is a liquid fat obtained from Olives. It is commonly used in cooking particularly, frying food or as a salad dressing. Despite the wide consumption of black olive fruits and their oil in the study area, the nutritional values have not been sufficiently investigated. Therefore, the study was to determine the nutritional and proximate values of the black Olive oil sold in Ganawuri market in Riyom Local Government Area of Plateau State using standard laboratory methods. The result of nutritional analysis indicated that olive oil had crude fat of 65.77%, protein of 8.09% crude fibre of 0%, and carbohydrate of 6.12%. The proximate analysis indicated that the olive oil had no calcium and phosphorus as it was negative (-) or 0%. The consumption of black olive oil due to its nutritional benefits is therefore justified and should be encouraged.